Adoption of wheat varieties in Bangladesh: expert elicitation approach - Rashid, MA; Hossain, Tanvir MB (Bangladesh Journal of Agricultural Research, 2016)
The study was undertaken to find out variety wise adoption rate of wheat in Bangladesh through expert elicitation procedure. Many varieties have been developed by Wheat Research Centre (WRC) but in details of varietal information and adoption information database was not developed which is very important and valuable for the scientist and policy planner. This study through expert elicitation for constructing detail varietal development and adoption database is timely and necessary for the research institute. From all over the Bangladesh 14 experts was invited to share their valuable knowledge and experience on wheat cultivation and adoption in the country. The average age of the experts were 54 yrs and average experience on wheat adoption was 22.65 yrs. The wheat expert informed that 13 major varieties are adopted by the farmers in the recent year(2013-14). Among those varieties, BARI Gom 24 (Prodip) covered highest cultivated area (186026 ha) which shared 41.03% of total wheat cultivated area. BARI Gom 21 (Shatabdi), BARI Gom 26 and BARI Gom 23 (Bijoy) ranked 2nd, 3rd and 4th position according to the share of cultivated area covered. The seed production information showed that BADC the only wheat seed producer supplied 24912.60 mt of wheat seed in the year 2013-14. The trend of seed production by different wheat variety revealed that over the period 2010-14, the seed production of BARI Gom 24 (Prodip) increased and BARI Gom 21 (Shatabdi) decreased. Increased seed production trend of Prodip variety leaded to highest adopted area of that variety. The main reason behind highest adopted area of Prodip variety was its very attractive attributes like high yield, big spike, large grain and lodging tolerance character. Although the Prodip covered highest area but other newly developed variety like BARI Gom 25, BARI Gom 26, BARI Gom 27 and BARI Gom 28 were the most promising varieties which showed increasing adoption path among the expert. These varieties have very good potentiality due to having short duration, tolerance to terminal heat stress, tolerant to salinity and lodging attributes. Satisfying higher demand for wheat consumption and ensuring food security through providing alternative to rice are the major concerning issue of the policy planner and the scientist. Therefore, the study have been undertaken to fulfill this issues. Bangladesh J. Agril. Res. 41(3): 491-505, September 2016